Transparansi dan Akuntabilitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Indonesia: Systematic Literature Review - Dian Bayu Sulistyo; Dyah Mutiara Khayatun Nufus; Anwirotul Hidayah; Nur Intan Rochmawati; Sisca Septiani (Prodi PGSD Unsultra, 2026)
This systematic literature review aims to analyze the transparency and accountability of School Operational Assistance (BOS) fund management in primary and secondary education in Indonesia for the 2020-2025 period. Using the PRISMA protocol, this study identified 524 articles from Google Scholar, Garuda Portal, SINTA, and Scopus databases, of which 20 articles met the inclusion criteria. The findings indicate that the effectiveness of BOS fund management depends on three key factors: transparency, accountability, and the competence of human resources managers. Key challenges include delays in fund distribution, technical errors in applications (RKAS/ARKAS), and limited understanding of technical guidelines at the school level. Quantitative studies show that transparency contributes 51.2%, accountability 52.7%, and community participation 53.9% to mutual education, with a simultaneous influence of 62.9%. This review provides recommendations for improving BOS fund governance by ensuring the stability of RKAS/ARKAS implementation and expanding vendor coverage in SIPLah, especially for remote areas, through digital strengthening systems, increasing the capacity of school financial managers, and increasing stakeholder participation in planning and evaluating the use of BOS funds.